On star 5-colorings of sparse graphs - Choi, Ilkyoo; Park, Boram (Discrete Applied Mathematics, 2021)
A star k-coloring of a graph G is a proper (vertex) k-coloring of G such that the vertices on a path of length three receive at least three colors. Given a graph G, its star chromatic number, denoted χs(G), is the minimum integer k for which G admits a star k-coloring. Studying star coloring of sparse graphs is an active area of research, especially in terms of the maximum average degree of a graph; the maximum average degree, denoted mad(G), of a graph G is [Formula presented]. It is known that for a graph G, if [Formula presented], then χs(G)≤6 (Kündgen and Timmons, 2010), and if [Formula presented] and its girth is at least 6, then χs(G)≤5 (Bu et al., 2009). We improve both results by showing that for a graph G, if [Formula presented], then χs(G)≤5. As an immediate corollary, we obtain that a planar graph with girth at least 8 has a star 5-coloring, improving the best known girth condition for a planar graph to have a star 5-coloring (Kündgen and Timmons, 2010; Timmons, 2008).
Keywords: Active area; Graph G; K-coloring; Maximum average degree; Planar graph; Sparse graphs; Star chromatic numbers; Star-coloring; Maximum average degree; Sparse graph; Star 5-coloring; Star coloring